COVID-19 and the Transformation of Work Culture in India: A Sociological Review - Awasthi, Sharad Kumar; Dwivedi, Satyam; Sharma, Onima (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The COVID-19 pandemic has been a catalyst for unprecedented transformations in work culture across the globe, with India experiencing significant and unique changes due to its socio-economic diversity. This paper provides a sociological review of the changing dynamics of work in India during and after the pandemic. It explores the rapid shift towards remote working, the rise of the gig economy, increased digitalization, and the widening of social inequalities based on class, gender, and urban-rural divides. By applying key sociological theories and reviewing relevant literature, the paper highlights how these transformations have redefined the meaning of work, impacted labour relations, and influenced occupational identities. It further investigates how these changes have differentially impacted various segments of the workforce, such as white-collar professionals, informal workers, and women. The paper concludes with reflections on the long-term implications for Indian society and policy interventions needed to address the emerging challenges.